Research on Project Scheduling Problems and Project Management Systems for Product Development - Zhang, Liwan (2024 Second International Conference on Data Science and Information System (ICDSIS), 2024)
In today's rapidly changing business environment, the success of a product development project often depends on its ability to quickly adapt to market changes and deliver innovative solutions in a timely manner. In the face of such challenges, an accurate and flexible scheduling system and a comprehensive and efficient project management system are central elements to ensure that projects are completed on time, resources are fully utilized, and teams are kept in sync.First, let's explore what scheduling for a product development project is. In simple terms, scheduling is the process of determining the start and end dates of various tasks and activities in the product development process. An effective schedule ensures that resources are allocated appropriately, risks are minimized, and key milestones are met. However, creating and maintaining such a schedule is not straightforward; it involves understanding the scope of the project, identifying task dependencies, and accurately estimating time, personnel, and material resources.